Planejamento de preços de exportação em pequenas empresas - Barbosa, Antonio Andrade (2006)
This essay is intended to show the importance of the small business in the economic plan. In the Brazilian economy, it assumes a very important role; however, in what concerns to foreign trade, and in comparison with other Countries, it still has to grow, though it does have potential to develop. Believing on this export plan growth potential, this present study is intended to contribute to such development, by analyzing the export prices planning. It addresses the price formation strategy based on costs and market economic theory. It examines the costing methods and how they should be utilized in cost analysis for an effective export sale price planning. It proposes the costs strategic administration of costs based on the Target Costing, which, taking into consideration the market vision, does not miss the importance of profit planning for the company perpetuation. The Kaizen Costing brings to the company the thinking that it is always possible to improve the methods and processes. The Activity Based Costing (ABC), despite its difficult application in the small business, is analyzed under the standpoint of a tool to supply the information to the Value Engineering required by the Target Costing. Still in this cost administration context, specific export costs and their incentives are analyzed, as a way to obtain competitive edge by rationalizing the costs and optimizing the incentives. Tributary planning is also used in such thinking aiming at saving on taxes for the company. The work is concluded with a small business profile analysis, because an export sale price planning model is proposed based on this business and its owner s peculiar characteristics